Fungal diseases of watermelon in Morogoro urban, Tanzania - R. B. Mabagala, E.R. Mbega (Journal of Phytology, 2016)
A study to examine fungal diseases infecting watermelon (Citrullus lanatus Thunb.) plants in Morogoro urban, Tanzania was conducted in November, 2011. Forty eight watermelon samples with necrotic symptoms collected from randomly selected home gardens were tested for infection using the Blotter method. Identification of the detected fungi was done based on morphological characters of the mycelia and conidia Observed under the stereo and compound microscopes. The results indicated that, watermelon samples were infected by Alternaria alternata (96.7%), Cercospora citrullina (93.3%), Fusarium oxysporum (40%), Microphomina phaseolina (38.3%) and Cladosporium cucumevicum (14.2%). Such results implied that, a number of fungal pathogens infect watermelon in Morogoro urban district. This is the first report of these fungal pathogens in Tanzania. More work is therefore, needed to study the incidence, distribution and economical impact of diseases of watermelon caused by these fungal pathogens in different locations in the country.